How Stressors and Facilitators of Work–Family Dynamics Interrelate and Affect Psychological Outcomes in Farming Women: A Mixed-Methods Approach in Chile - Mora-Guerrero, G (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Background/Objectives: This study aimed to explore how stressors and facilitators within the work–family interface (WFI) influence mental health outcomes among farming women in rural Chile. The research sought to identify key relational patterns and contextual determinants shaping psychological well-being in this population. Methods: An exploratory mixed-methods design was employed, involving 41 semi-structured interviews analyzed using grounded theory. Qualitative themes were quantified by calculating the percentage of occurrence per interview, allowing for comparative analysis. Pearson correlation and principal component analysis (PCA) were used to examine associations among WFI dimensions and mental health-related variables. Results: Strong and statistically significant correlations emerged between institutional and community facilitators (r = 0.664, p < 0.01) and between gender facilitators and family workload stressors (r = 0.609, p < 0.01). PCA revealed two distinct patterns: women who rely on institutional support often resist traditional family roles, while others find balance through familial support systems. The gendered distribution of caregiving and productive tasks was a key factor in psychological well-being, with some women reporting physical discomfort linked to triple workloads. Conclusions: The dynamics of the WFI in rural contexts are shaped by both sociocultural and institutional factors. The findings highlight the need for culturally sensitive mental health policies that acknowledge and respond to the lived experiences of farming women. © 2025 by the authors.
Keywords: work-family interface (WFI); rural mental health; sociocultural mediators; gender-based dynamics; community facilitators